Pemikiran Pendidikan Islam Prof. H. Muzayyin Arifin, M.Ed dan Relevansinya di Era Modern - Siti Rodhiatun Faizah (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2021)
The study explains the Islamic education thinking of Prof. H. Muzayyin Arifin, M.ED. and its relevance in the modern age. His goal is to know the biography of Prof. H. Muzayyin Arifin, M.ED, Islamic education thinking Prof. H. Muzayyin Arifin, M.ED., dan its relevance in the modern age. The study uses library research methods with a descriptive approach. The study of Muzayyin Arifin’s thinking on Islamic education was that the correct science in his view was that it benefited many fields of modern life, both theoretical and practical. The ultimate goal of Islamic education is to achieve happiness in the world and the afterlife. The curriculum is viewed as both comprehensive and integrated with the purpose of Islamic education, as well as covering general and religious science. Educators should use principled methods of education in child-centered, that learners are more important than the educators themselves. The evaluation in Islamic education is the assessment technique on the behavior of learners based on comprehensive standards of accounting for all aspects of both religion and psychological life. The relevance of Islamic education thinking Muzayyin Arifin is in harmony with Indonesia’s rules of education.